Investigating the roles of cytokines and chemokines in pregnancy-related toxemia - Adedeji Okikiade; Chidinma Kanu; Oluwadamilare Iyapo; Ololade Omitogun (Medical Laboratory Journal, 2025)
Background: Hypertensive disorders, particularly preeclampsia (PE), complicate 2–8% of pregnancies and significantly contribute to maternal and perinatal mortality. PE disproportionately affects low-resource regions, accounting for 26% of maternal deaths in Latin America and 9% in Africa and Asia. Risk factors include extreme maternal age, chronic hypertension, obesity, diabetes, and racial disparities (Higher incidence in Black and Hispanic populations). The exact cause remains unclear, but angiogenic imbalance and immune dysregulation play key roles. This review focuses on the role of cytokines and chemokines in developing preeclampsia (PE). Methods: A narrative review was conducted to examine studies on the immunological and vascular mechanisms of preeclampsia, with a focus on recent systematic reviews and high-impact research. Results: The results highlighted a critical imbalance between pro-inflammatory (IL-6, TNF-α) and anti-inflammatory (IL-4, IL-10) cytokines in PE pathogenesis. Notably, reduced second-trimester IL-10 levels served as an early predictive biomarker. Endothelin-mediated vasoconstriction and Th1/Th2 immune imbalance further exacerbated endothelial dysfunction, a central feature of PE. While human and animal studies support these findings, precise mechanistic pathways remain elusive. Conclusion: Cytokine and endothelin can serve as promising biomarkers and therapeutic targets for PE. Early IL-10 detection may improve risk prediction, but no causal links have been confirmed yet. Gaining a better understanding of these mediators could improve clinical strategies and help minimize complications. Future longitudinal research should focus on biomarkers and explore anti-inflammatory treatments for PE prevention.